Artesunate Regulates Neurite Outgrowth Inhibitor Protein B Receptor to Overcome Resistance to Sorafenib in Hepatocellular Carcinoma Cells - He, Wubin; Huang, Xiaoxu; Berges, Bradford K.; Wang, Yue; An, Ni; Su, Rongjian; Lu, Yanyan (Frontiers in Pharmacology, 2021)
Sorafenib, a multireceptor tyrosine kinase inhibitor is FDA approved first-line drug for the treatment of advanced liver cancer and is reported to extend the overall survival in individuals with advanced hepatocellular carcinoma (HCC). However, the primary or acquired resistance to sorafenib is gradually increasing, leading to failure of HCC treatment with sorafenib. Therefore, it is very crucial to study the potential mechanism of sorafenib resistance. Our current results show that NgBR has overexpressed in sorafenib resistant cells and its expression level was negatively correlated with the sensitivity of liver cancer cells to the sorafenib. Artesunate can inhibit the expression level of NgBR. Sorafenib in combination with Artesunate overcome the HCC resistance to sorafenib.